Biases in Corporate Income Tax-CIT - AGOSSADOU, STANISLAS T MEDARD D C (LAP LAMBERT Academic Publishing, 2024)
This book analyzes the biases in Corporate Income Tax (CIT) in the countries of the world. Content analysis was applied to tax codes. The sample covers the tax codes in force for the year 2023 in ten countries in Africa, America, Asia and Europe. Assuming that corporate tax is the cost of using public capital, the analysis of the content of these tax codes focused on corporate income tax. Several biases in CIT have been identified and relate to financing, investment, result, rate and tax base. This book is one of the first to expand the literature by analyzing the biases in CIT, likely to affect tax behavior and, by extension, the financial behavior of firms.